Artificial spawn generation based on alginate encapsulated mycelium as inoculum for mushroom cultivation - Ortiz, Gastón Ezequiel (2017)
Spawn quality is an important factor that affects the final yield in mushroom production. One of the most common risks is the contamination of substrates and spawn by mitosporic fungi. Some species do not easily grow on grain substrate as traditional species do and these find it real difficult to produce spawn. A method was evaluated to produce spawn for mushroom production based on aseptically encapsulated mycelium using alginate beads. Strains of four selected edible mushrooms were cultivated in liquid medium, mycelium was harvested by filtration. Subsequently, it was blended with 100 mL of 2% (w/v) sodium alginate solution or with the alginate solution with the addition of 2% (w/v) yeast extract solution or with the addition of 2% (w/v) meat extract solution. An electronic mixer was used to disaggregate the mycelium and generate a homogeneous suspension. To obtain the artificial spawn, the cells suspensions were dripped in 200 mL of 500 mM CaCl2 solution using a cut micro-tip. Beads obtained were inoculated in potato dextrose agar Petri dishes and in substrate (wheat straw or Poplar sawdust) to evaluate the growth. Tests carried out using this method, demonstrated that the incorporation of a suitable nutrient increases the ability of selected mushroom to emerge from the beads. Mycelia colonization tests were carried out on sterilized substrate, one using alginate beads and another one using the traditional spawn as inoculum. No significant differences according to t-test (p<0.05) were shown. However, spawning production based on alginate beads can be performed in only a few days, whereas the traditional method requires more time. The method proposed here represents an antecedent to improve spawn generation for future industrial applications, for further studies and for other uses as mycelium inoculant.